2019
DOI: 10.4103/jmas.jmas_264_17
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of transoral endoscopic parathyroidectomy through vestibular route for primary sporadic hyperparathyroidism: A South Indian experience

Abstract: Through this study, we opine that this novel transoral vestibular route parathyroidectomy is a feasibly applicable approach for primary sporadic hyperparathyroidism, especially with solitary benign adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, the feasibility of parathyroidectomy by the transoral vestibular approach has also been demonstrated by several groups. 23,24 Bhargava et al have also demonstrated that with proper case selection, the transoral TOEPVA technique is an alternative for parathyroidectomy especially for unigland sporadic primary hyoerparathyroidism. 25 Transient recurrent laryngeal nerve palsy was reported in one case by Karakas et al One of our patients who developed recurrent laryngeal nerve paresis in the postoperative period recovered over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the feasibility of parathyroidectomy by the transoral vestibular approach has also been demonstrated by several groups. 23,24 Bhargava et al have also demonstrated that with proper case selection, the transoral TOEPVA technique is an alternative for parathyroidectomy especially for unigland sporadic primary hyoerparathyroidism. 25 Transient recurrent laryngeal nerve palsy was reported in one case by Karakas et al One of our patients who developed recurrent laryngeal nerve paresis in the postoperative period recovered over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…No mental nerve injury or infections were seen. Recently, another report from India was published[ 13 ]. This study included 12 patients with PHPT who underwent transoral endoscopic vestibular parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Transoral parathyroidectomy was first described through the mouth floor but was not widely accepted due to complications and poor patient compliance[ 7 - 9 ]. Endoscopic transoral vestibular parathyroidectomy is a feasible and safe technique, which provides a direct approach to the glands with excellent cosmetic results[ 10 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…After thyroid diseases, hyperparathyroidism is one of the most common endocrine surgical disease [1]. It occurs either from a disorder within the parathyroid glands (primary hyperparathyroidism) or disorder outside the parathyroid glands (secondary or tertiary hyperparathyroidism) [2].…”
Section: Introductionmentioning
confidence: 99%
“…After, realisation of that a single adenoma is the cause of hyperparathyroidism in most of the patients (80-85%), surgical management was changed significantly [2]. With preoperative imaging tools (ultrasound and technetium-99m sestamibi scintigraphy) for localisation of the adenoma and intraoperative parathyroid hormone level measurements for confirmation, surgical excision of the offending parathyroid adenoma is still accepted as the main treatment of primary hyperparathyroidism [1,2,5].…”
Section: Introductionmentioning
confidence: 99%